Nowe horyzonty misji „Ad gentes” – normy prawa kanonicznego - Domaszk, Arkadiusz (Prawo Kanoniczne, 2010)
The mission of Church directed to non- believers didn’t finish. It still lasts. The mission ad gentes is topical, because 4 million people hadn’t believed in Jesus Christ. Also series of Magisterium of the Church documents from the last decades affirm the need to continue missionary work, including traditional distinguishing countries or missionary areas. At the same time the change of the modern world significantly influence on other parallel picture of the mission ad gentes. The processes of developing large cities and agglomerations as well as migrations of people constitute new challenge to Church and its Gospel ministry. These are new horizons of the mission ad gentes. Also the world of social mass media and other cultural areopaguses of the modern world belong to those new missionary spaces. The missionary work of Church (ad gentes) is present for a long time in common law (e.g. The Code of Canon Law 1983 and numerous instructions about above mentioned) and in particular law. Whereas the issue considering new missionary horizons, pointed out in Magisterium of the Church documents, is only partly regulated by the canon law. Pastoral activities have to respond to new challenges (large cities and the migration) as well as to presence of non- Christians in traditionally Christian countries. The Church uses social mass media in evangelization. It finds it response additionally in the canon law. The idea (on a legal ground) of introducing the Gospel into the media environment or other cultural spaces is less noticeable.